2019
DOI: 10.1080/21663831.2019.1650130
|View full text |Cite
|
Sign up to set email alerts
|

A eutectic high-entropy alloy with good high-temperature strength-plasticity balance

Abstract: We developed a eutectic high-entropy alloy (EHEA) with appreciable high-temperature strengthplasticity balance. Structural characterizations of the as-cast sample revealed a lamellar structure with austenite (face-centered-cubic, FCC) and Laves phases. Upon annealing at 873 K, precipitation of nanoscale (Ni, Al, and Zr)-rich L1 2 phase from the FCC phase took place, which eventually transformed into a martensitic (hexagonal,) phase with rearrangement of atomic species. Compressive properties revealed a brittle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Also, it has been demonstrated that a minor addition of Al (1.7 at. %) to the non-equimolar Co 27 Cr 21 Fe 18 Ni 24 Ta 10 EHEA promoted the formation of a high-density L1 2 ordered nano-precipitates [16]. The coherently ordered L1 2 precipitates were found to be thermodynamically stable against high-temperature annealing, which offered an effective strain hardening source to counteract against softening at elevated temperatures [16].…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…Also, it has been demonstrated that a minor addition of Al (1.7 at. %) to the non-equimolar Co 27 Cr 21 Fe 18 Ni 24 Ta 10 EHEA promoted the formation of a high-density L1 2 ordered nano-precipitates [16]. The coherently ordered L1 2 precipitates were found to be thermodynamically stable against high-temperature annealing, which offered an effective strain hardening source to counteract against softening at elevated temperatures [16].…”
Section: Introductionmentioning
confidence: 98%
“…%) to the non-equimolar Co 27 Cr 21 Fe 18 Ni 24 Ta 10 EHEA promoted the formation of a high-density L1 2 ordered nano-precipitates [16]. The coherently ordered L1 2 precipitates were found to be thermodynamically stable against high-temperature annealing, which offered an effective strain hardening source to counteract against softening at elevated temperatures [16]. However, the Co 27 Cr 21 Fe 18 Ni 24 Ta 10 EHEA with a minor addition of Al exhibited typical Laves + FCC eutectic structure formed during the conventional solidification process, and the long-striped Laves phase was found to cause early crack initiation during compression, leading to a prevailing brittle fracture at high temperatures [16].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations